2020
DOI: 10.3390/ma13235540
|View full text |Cite
|
Sign up to set email alerts
|

A New Preparation Method of Cement with Photocatalytic Activity

Abstract: The studies of some mechanical properties and photocatalytic activity of new cements with photocatalytic activity are presented. The new building materials were obtained by addition of semi-product from titanium white production. Semi-product was calcined at 300 and 600 °C for one, three, and five hours and then this material was added to cement matrix in an amount of 1 and 3 wt.%. New materials were characterized by measuring the flexural and compressive strength and the initial and the final setting time. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…There are many literature reports on the excellent properties of cement materials, such as air purification [ 3 , 7 , 16 , 17 , 19 , 23 , 24 , 104 , 105 ], self-cleaning [ 6 , 8 , 12 , 25 , 32 , 37 , 38 , 39 , 40 , 106 ], and self-sterilization [ 4 , 62 , 103 ]. However, despite many advantages, the wide application of photocatalytic technology in civil engineering practice is still limited [ 28 ].…”
Section: Results Of Mechanical Properties Of Modified Cement Mortarsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many literature reports on the excellent properties of cement materials, such as air purification [ 3 , 7 , 16 , 17 , 19 , 23 , 24 , 104 , 105 ], self-cleaning [ 6 , 8 , 12 , 25 , 32 , 37 , 38 , 39 , 40 , 106 ], and self-sterilization [ 4 , 62 , 103 ]. However, despite many advantages, the wide application of photocatalytic technology in civil engineering practice is still limited [ 28 ].…”
Section: Results Of Mechanical Properties Of Modified Cement Mortarsmentioning
confidence: 99%
“…Wang et al [ 130 ] showed that the addition of NT reduces the initial setting time by about 40 min, from 190 min for cement without NT addition to about 150 min for cement with 5 wt% TiO 2 . On the other hand, Janus et al [ 104 ] reported that the addition of an intermediate from the production of titanium white with the sulfate method, in the amount of 1 and 3 wt.% modified at 300 °C slightly increases the initial and final setting time compared to unmodified cement, on average by 30 min initially and the final one by about 50 min. On the other hand, for TiO 2 modified at 600 °C, the initial one was on average 40 min longer, and the final one was about 70 min longer.…”
Section: Results Of Mechanical Properties Of Modified Cement Mortarsmentioning
confidence: 99%
“…In our previous work [3], the NO gas (1.989 ppm ± 0.040 ppm, Air Liquide, Kraków, Poland) was used as model pollution in photocatalytic tests. NOx removal was evaluated using the experimental installation, a scheme of which is presented in Figure 1.…”
Section: Photocatalytic Activity Of the Investigated Materialsmentioning
confidence: 99%
“…Currently, an important argument in favor of its use is the contribution to protecting the natural environment [1,2]. TiO 2 is a photocatalyst that is often added to various types of building materials, such as glass, cement, gypsum and others, in order to give them self-cleaning properties, as well as to make them able to clean the air from pollutants [3,4]. We can distinguish three main methods of obtaining photoactive building materials.…”
Section: Introductionmentioning
confidence: 99%
“…TiO 2 nanoparticles are added to the concrete mix and therefore are incorporated within the bulk material. Only a fraction of those particles is allocated at the material–atmosphere interface and hence can be exposed to light to undergo photocatalytic reactions. Often an enhancement of mechanical properties by influencing the hydration mechanism of clinker phases is targeted and achieved as well …”
Section: Introductionmentioning
confidence: 99%